Paul and the rhetoric of reconciliation an exegetical investigation of the language and composition of 1 Corinthians - Mitchell, Margaret M. 1956- (Louisville, KY Westminster/John Knox, 1993)
Includes bibliographical refererences and indexes.
Revision of the author's thesis (doctoral - Chicago), 1989. First published Tubingen, Germany, by J.C.B. Mohr (Paul Siebeck), 1992.
Keywords: Rhetoric in the Bible; Bible. N.T. Corinthians 1st -- criticism, interpretation, etc